Jewels of the Qila : the remarkable story of an Indo-Canadian family - Johnston, Hugh J. M., 1939- (UBC Press, 2011)
"Hugh Johnston draws on memoirs and interviews, newspaper articles and photographs, to tell the story of three generations of a remarkable Sikh family and the communities they lived in and supported in both Canada and India. The Siddoos are Punjabi. Kapoor Singh, father and grandfather, arrived in British Columbia in 1912 and overcame racial prejudice and legal discrimination to transform himself from day labourer to lumber baron, publisher, philanthropist, and community leader"--Provided by publisher